TYPES OF RARE-EARTH ELEMENT DISTRIBUTION AND PETROGENESIS OF GRANITOID ROCKS - Nozhkin A.D.; Turkina O.M.; Bobrov V.A. (My University, 1989)
For the Yenisey Ridge, a region with a very complete Precambrian section in the southwestern part of the Siberian craton, we have analyzed the REE-distribution in granitoid rocks of genetically different types. These crustal rocks developed in two principal stages, in Early and Late Proterozoic time, respectively, within a sialic block, where the high level of geochemical differentiation and degree of maturity of the material govern the relatively high background concentrations of thorium and REE in granite. A characteristic feature of each stage of silicic magmatic activity is the change from autochthonous palingenic or metasomatic granitoid rocks to parautochthonous palingenic and allochthonous, intrusive-magmatic varieties. There are also asynchronous bodies and granite-gneiss domes, where the granitoids had an inherited evolution and were formed from autochthonous to allochthonous facies. Allochthonous granitoid rocks that are greatly removed from the level of melt generation have V-shaped distribution curves of REE, whose content, in addition to that of thorium, reflects the degree of enrichment of the deep magma source in sialic or femic material. The low ratio of cerium- to yttrium-group rare earths and the sharply negative europium anomaly are due to intensive differentiation of the melts.
Keywords: Precambrian; Proterozoic; Precambrian::Proterozoic; Precambrian; Докембрий::Протерозой; Докембрий